Hubungan Intensitas Menonton Konten Memasak di TikTok dengan Motivasi Belajar Memasak Remaja Putri di Desa Tulungrejo - Dwi Apriliani; Nugrahani Astuti; Lucia Tri Pangesthi; Ita Fatkhur Romadhoni (Universitas Maritim AMNI Semarang, 2023)
This study aims to determine whether there is a relationship between the intensity of watching cooking content on TikTok and the motivation to learn cooking for young women in Tulungrejo village. This research is a descriptive research with a quantitative approach. The data collection technique used was a questionnaire distributed to 110 young women in Tulungrejo Village as a sample. Data analysis used the product moment correlation, which previously carried out the prerequisite test using the normality test and linearity test. The results showed 1) the intensity of watching cooking content on Tulungrejo village girls' TikTok with a high intensity of 33%, medium 67% and low 0%. 2) The motivation to learn cooking for young women in Tulungrejo village with high motivation is 76%, medium is 24%, and low is 0%. 3) Based on the results of hypothesis testing with the product moment correlation formula, an r-count value of 0.600 is obtained with an r-table price at a significance level of 5%, namely 0.187 so that 0.600> 0.187. It can be concluded that Ha is accepted and Ho is rejected, so there is a positive relationship between the intensity of watching cooking content on TikTok and the motivation to learn cooking for young women in Tulungrejo village.